Different Nitrogen Sources Fuel Symbiotic Mussels at Cold Seeps - Wang, Fuqiang; Wu, Ying; Feng, Dong (Frontiers in Marine Science, 2022)
Cold seeps globally host dense unique oasis-type ecosystems, mainly fuelled by chemosynthetic microorganisms via reduced gases such as methane and hydrogen sulfide. However, the origin and pathway of nitrogen chemosynthesis in this widely distributed symbiont ecosystem remain poorly understood. Here, we explore biomarker methods (bulk stable isotope, amino acid (AA), fatty acid (FA) and compound-specific isotope analyses in gill tissues of mussels) to demonstrate the relative contributions of inorganic and organic nitrogen to symbiotic mussels at cold seeps in the South China Sea and their impact on the synthesis and metabolism of amino acids. Gigantidas platifrons (G. platifrons) symbioses with type II methanotrophs via the Serine pathway, and Bathymodiolus aduloides (B. aduloides) thrives with sulfur-oxidizing bacteria via the Calvin pathway, as revealed by bulk δ13C and δ13C of FAs. Based on the δ15N values in gill tissues of mussels, organic nitrogen from sediment is estimated as the dominant nitrogen source for B. aduloides (97-98%), in contrast, NH4+ was the main nitrogen source for G. platifrons. Different dominant nitrogen sources result in the δ15N of AAs in the gills of two mussel species having opposite trends, which might be related to synthesis and metabolism of AAs in symbiotic bacteria and host, respectively. Our findings reveal that the mechanism of nitrogen acquisition in cold seep systems is plastic and related to DIN sources/uptake and changing environmental conditions. These findings uncover novel biosynthesis of nitrogen in the deep sea, typically at cold seeps, and may have important implications for nitrogen biogeochemistry and deep-sea conservation.